O Rio do Peixe e o desenvolvimento urbano da cidade de Joaçaba, SC - Frantz, Milton Walter (2008)
The urban development of the river basin valley of Rio do Peixe in the state of Santa Catarina was always directly linked to the conditions and possibilities created by the hydric resources and their topographical characteristics influencing the installation of the infrastructure of transports and energy. The city of Joaçaba, located in the center of the valley, it is strategic point in this study, having been stage of the construction of the first bridge, integration factor between the west and the coast of the state of Santa Catarina. Rio do Peixe always acted as decisive agent in the strategies of regional development. As one of the main positive impacts that Rio do Peixe brought about the urbanization of Joaçaba mentioned the own plan proposed for the railroad justifying the allocation of resources and implantation of development politics in the area. We can still detach the exploration of his hydroelectric potential, supplying cheap energy, facilitating the industrialization process; until the end of the decade of seventy it was great leisure and entertainment element; for the perpetuity, it is constituted of constant source of water for consumption and industrial use; for the depth of the gutter, allow occupation to his margin. In this work identified and evaluated the influence, of Rio do Peixe as factor of urban development of the city of Joaçaba, seeking the urban planning and to the maintainable handling of the urbanized areas and of the natural resources. He stood out in the it analyzes of the legislation the legal superposing, when we confronted with the application of the forest code in urban areas to the detriment of the application of the foreseen in the law of fragmentation of the urban soil. The legal superposing generates conflicts among laws with the same hierarchical position, doing with that the sentences of the judiciary more and more seek protection in the laws environmentally more restrictive. It was observed through the analysis of the results that is necessary the elaboration of specific urban regulation for the riverine areas, that they allow his environmental another qualification, and at the same time return the river the city, as urban reference